Enhancement of Electrical and Optical Properties of Polyvinylidene Fluoride Samples by Cerium Sulfate Addition - Falcão, E.A.; Amorim, M.J.R.; Botero, E.R.; Domingues, N.L.C.; Santos, I.A.; Rinaldi, A.W. (Journal of Composites and Biodegradable Polymers, 2023)
In the present work, polyvinylidene fluoride’s (PVDF) electrical and optical properties have been studied as a function of cerium sulfate tetrahydrate called Ce(SO4)2. Experimental result shows that the relative percentage of β phase (Fβ%) increases by almost 55 % with Ce(SO4)2 addition in the polymeric matrix. The dielectric permittivity measurements presented an increase, at 1 KHz, of 62% up to 0.8% of Ce(SO4)2 content. This increase was attributed to the Maxwell-Wagner effect. The UV-Vis measurements presented some changes at the UV region due to Ce(SO4)2. The fluorescence measurements showed an enhancement in the fluorescence peak of almost 130 % for the PVDF/Ce(SO4)2 0.8% and a blue shift of the maximum fluorescence intensity. These results show that PVDF/Ce(SO4)2 sample is a potential candidate for optical, photonic, electrical, and electronic applications.